OP0005 Leflunomide reduces transendothelial migration. (1st June 2001) - Grisar, J; Stummvoll, GH; Eselböck, D; Pietschmann, P; Smolen, JS
Abstract : Background: The disease modifying drug leflunomide is widely used in the therapy of rheumatoid arthritis (RA). Its active metabolite, A771726, leads to inhibition of dihydroorotate dehydrogenase, an enzyme necessary for pyrimidine de-novo synthesis. Since activated lymphocytes expand their pyrimidine pool, A771726 decreases their proliferation. A771726 also suppresses TNF mediated nuclear factor kappaB activation. We were therefore interested if A771726 also would be capable to influence transendothelial migration (TEM) of peripheral mononuclear cells (PBMC). Objectives: Methods: We investigated the TEM of PBMC, which migrated through endothelial cell monolayers in an in-vitro model. Human umbilical vein endothelial cells (EC) were cultured to confluence on collagen gels and then incubated with human PBMC of healthy blood donors. PBMC were recollected in three groups: 1) cells that did not adhere to the endothelium, 2) cells that bound to the endothelium, 3) cells that had migrated through the endothelium, and then counted by microscope. Experiments in which EC and PBMC as well as only EC were treated with A771726 (in the absence or presence of uridine) were compared to simultaneously performed control experiments. No increased toxicity on the PBMC treated with the doses of A771726 used in our experiments, was observed. Paired T Test was used for statistical evaluations. Results: 24 h incubation of PBMC and EC with A771726 induced a significant decrease in TEM (8 ± 6% vs. 16 ± 12% migrated cells, p = 0.004). Furthermore, 24 h preincubation of solely the EC with A771726 inhibited the TEM of untreated PBMC (11 ± 9% vs. 15 ± 8% migrated cells, p = 0.043), indicating direct effects of A771726 on EC. Uridine significantly reversed the decrease in TEM when incubating PBMC and EC with both uridine and A771726 (15 ± 10% vs 9 ± 7% migrated cells, p = 0.023). Conclusion: Our results demonstrate that leflunomide may have direct anti-inflammatory effects by inhibiting the extravasation of PBMC, possibly via downregulation of adhesion molecules on EC and mononuclear cells. These data suggest, that leflunomide, besides its influences on lymphocyte proliferation, also reduces recruitement of mononuclear cells to inflammatory sites.